2016
DOI: 10.1038/srep31107
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Autism Motor Signature: Gesture patterns during smart tablet gameplay identify children with autism

Abstract: Autism is a developmental disorder evident from infancy. Yet, its clinical identification requires expert diagnostic training. New evidence indicates disruption to motor timing and integration may underpin the disorder, providing a potential new computational marker for its early identification. In this study, we employed smart tablet computers with touch-sensitive screens and embedded inertial movement sensors to record the movement kinematics and gesture forces made by 37 children 3–6 years old with autism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
160
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(176 citation statements)
references
References 77 publications
(115 reference statements)
9
160
0
7
Order By: Relevance
“…Our findings were consistent with prior studies showing increased variability of manual motor output in ASD during precision gripping [16,17,39], writing [13], object lifting [40,41] and the use of simple finger gestures [44]. As the task of isometric index finger abduction only involves the FDI muscle, our study suggests that failure to precisely adjust force control and motor output in response to visual feedback is evidenced even when actions are restricted to a single muscle group as opposed to requiring coordination across different effectors or muscles.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were consistent with prior studies showing increased variability of manual motor output in ASD during precision gripping [16,17,39], writing [13], object lifting [40,41] and the use of simple finger gestures [44]. As the task of isometric index finger abduction only involves the FDI muscle, our study suggests that failure to precisely adjust force control and motor output in response to visual feedback is evidenced even when actions are restricted to a single muscle group as opposed to requiring coordination across different effectors or muscles.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormalities in postural stability have been documented using an electronic balance board (Nintendo Wii), which showed that autistic participants had more difficulty maintaining balance (Travers, Powell, Klinger, & Klinger, 2013). Discriminant analysis has shown that autistic children can be sensitively and specifically classified according to the speed, force and pressure of their finger movements on a tablet screen (Anzulewicz, Sobota, & Delafield-Butt, 2016); machine learning was also seen to correctly identify them by the kinematics of reach-to-drop (Crippa et al, 2015) and reachto-throw tasks (Perego, Forti, Crippa, Valli, & Reni, 2009). Other studies of kinematics in very basic arm movements and reaching and grasping reveal differences between autistic and TD participants (Campione, Piazza, Villa, & Molteni, 2016;Cook, Blakemore, & Press, 2013).…”
mentioning
confidence: 99%
“…Third, there remains a lack of clear understanding of the technique that is being used. A number of studies used multiple algorithm approaches and report on the highest predictive value [32,33,36,37,43,44,48,49]. Before arguing on the best algorithm to use, it would be important to understand why there are such differences in the results and the reason as to which approach would be most appropriate depending on the characteristics of the dataset and what sort of an output one is trying to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers have attempted to capture differences in movement patterns to use as a distinctive characteristic of ASD [41,42]. Studies by Li et al [43] and Anzulewicz et al [44], each used imitation based on observation and gesture patterns using smart tablet devices to detect kinematic parameters to use for classifying between ASD and non-ASD.…”
Section: Motor Movementsmentioning
confidence: 99%